Characterisation, Analysis and Design of Hydrated Cement Treated Crushed Rock Base as a Road Base Material in Western Australia - Jitsangiam, Peerapong; Nikraz, Hamid; Siripun, Komsun; Chummuneerat, Suphat (David Publishing Company, 2012)
Hydrated Cement Treated Crushed Rock Base (HCTCRB) is widely used as a base course in Western Australian pavements. HCTCRB has been designed and used as a basis for empirical approaches and in empirical practices. These methods are not all-encompassing enough to adequately explain the behaviour of HCTCRB in the field. Recent developments in mechanistic approaches have proven more reliable in the design and analysis of pavement, making it possible to more effectively document the characteristics of HCTCRB. The aim of this study was to carry out laboratory testing to assess the mechanical characteristics of HCTCRB. Conventional triaxial tests and repeated load triaxial tests (RLT tests) were performed. Factors affecting the performance of HCTCRB, namely hydration periods and the amount of added water were also investigated. It was found that the shear strength parameters of HCTCRB were 177 kPa for cohesion (c) and 42° for the internal friction angle (f). The hydration period, and the water added in this investigation affected the performance of HCTCRB. However, the related trends associated with such factors could not be assessed. All HCTCRB samples showed stress-dependency behaviour. Based on the stress stages of this experiment, the resilient modulus values of HCTCRB ranged from 300 MPa to 1100 MPa. CIRCLY, a computer program based on the multi-layer elastic theory was used in the mechanistic approach to pavement design and analysis, to determine the performance of a typical pavement model using HCTCRB as a base course layer. The mechanistic pavement design parameters for HCTCRB as a base course material were then introduced. The analysis suggests that the suitable depth for HCTCRB as a base layer for WA roads is at least 185 mm for the design equivalent standard axle (ESA) of 10 million.